Ritual Perkawinan Adat dan Penalaran Hukum Islam: Analisis 'Urf tentang Tradisi Nipa'bajikang di kalangan Komunitas Muslim di Kabupaten Gowa - Amelia, Reski; Chotban, Sippah (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
This article discusses the traditional Nipa'bajikang wedding ritual practiced by the Je'ne Madingin Muslim community in Gowa Regency, Indonesia, within the framework of Islamic law reasoning based on the concept of 'urf. The main problem of this research is how the position of the Nipa'bajikang tradition in Islamic law and the extent to which the practice of the ritual can be classified as 'urf sahih or 'urf fasid. This research aims to analyze the form and meaning of the implementation of the Nipa'bajikang ritual, examine the views of religious leaders on the tradition, and assess its conformity with the principles of Islamic sharia through the 'urf approach. The research method used is qualitative with a descriptive-analytical approach. Data was obtained through field observations, in-depth interviews with traditional leaders, religious leaders, and communities, and documentation studies. The analysis was carried out by examining ritual practices against the principles of monotheism, prayer orientation, and benefit as the main parameters in the theory of 'urf. The results of the study show that the Nipa'bajikang ritual is understood and carried out as a medium of prayer and plea for blessings to Allah SWT., without belief in the supernatural power in the symbolic elements used. In addition, this ritual serves to strengthen ukhuwah, ta'awun, and social solidarity in the local Muslim community. Based on the criteria of 'urf, the tradition of Nipa'bajikang is categorized as 'urf sahih because it fulfills the elements of social enforcement, utility, and conformity with the principles of Islamic law. The implications of this study confirm the relevance of the concept of 'urf as a socio-legal framework in assessing local cultural practices and supporting the development of contextual Islamic legal reasoning in Indonesian Muslim society.